THE PERCEPTIONS OF ISLAMIC BANKERS ON QARDHUL HASAN IN MALAYSIAN ISLAMIC BANKS - Noraini Mohd. Ariffin, Muhammad Akhyar Adnan (Kulliyyah of Economics and Management Sciences, 2010)
This research study deals with the perceptions of Islamic bankers on the issue of Qardhul Hasan in Islamic banks in Malaysia. The study adopted the methodology of questionnaire survey. 13 full-fledged Islamic banks in Malaysia are used in the study. The response rate is 46.9%. The findings are divided into three sections: Knowledge and awareness about Qardhul Hasan, General Information on Qardhul Hasan, Problems of Qardhul Hasan and Differences in Perceptions among the Islamic bankers. In general, the Islamic bankers are familiar with Qardhul Hasan and they agreed that Islamic banks should offer Qardhul Hasan in order to enhance corporate social responsibility and to help needy people. Therefore, the findings could provide insights to Islamic banks in diversifying their products by offering Qardhul Hasan to the customers but with proper guidelines and policies.